EDUKASI LITERASI KESEHATAN MENTAL BERBASIS DIGITAL MELALUI PENGENALAN PLATFORM DETEKSI DINI PADA GENERASI Z - Irmma Dwijayanti; Alfirna Rizqi Lahitani; Kartikadyota Kusumaningtyas; Muhammad Habibi; Kharisma (Jurnal Berdaya Mandiri, 2025)
Mental health education in Z Generation still receives less attention, even though mental health disorders in adolescents can develop into serious problems if not treated early. Many students do not understand or recognize the early symptoms of mental health disorders, and there is a lack of school involvement in providing related education. Technology can be a solution to help with early detection, one of which is through the Beck Depression Inventory (BDI)-based platform from Pijar Psikologi. This activity is expected to provide an understanding of the importance of mental health and how to recognize the early symptoms of mental health disorders. Pengabdian kepada Masyarakat (PkM) activity aims to introduce early detection tools for mental health disorders for students of SMK N 02 Yogyakarta. The methods used include pre-test, socialization and dissemination of research results, the practice of using early detection platforms, and post-test. Based on the results of the comparative analysis of pre-test and post-test scores, there was an increase in participants' knowledge regarding mental health by 90%. This shows that the delivery of the material provided is effective in increasing participants' knowledge. This increase in knowledge can be the basis for students to become cadres who are directly involved in disseminating digital literacy related to the use of information technology in mental health. Keyword: mental health, mental health education, Z generation, early detection tools